Severe lymphopenia during neoadjuvant chemoradiation for esophageal cancer: A propensity matched analysis of the relative risk of proton versus photon-based radiation therapy. Issue 1 (July 2018) - Shiraishi, Yutaka; Fang, Penny; Xu, Cai; Song, Juhee; Krishnan, Sunil; Koay, Eugene J.; Mehran, Reza J.; Hofstetter, Wayne L.; Blum-Murphy, Mariela; Ajani, Jaffer A.; Komaki, Ritsuko; Minsky, Bruce; et al.
Abstract: Background and purpose: Circulating lymphocytes are exquisitely sensitive to radiation exposure, even to low scattered doses which can vary drastically between radiation modalities. We compared the relative risk of radiation-induced lymphopenia between intensity modulated radiation therapy (IMRT) or proton beam therapy (PBT) in esophageal cancer (EC) patients undergoing neoadjuvant chemoradiation therapy (nCRT). Material and methods: EC patients treated with IMRT and PBT were propensity matched based on key clinical variables. Treatment-associated lymphopenia was graded using CTCAE v.4.0. Using matched cohorts, univariate and multivariable multiple logistic regression was used to identify factors associated with increased risk of grade 4 lymphopenia as well as characterize their relative contributions. Results: Among the 480 patients treated with nCRT, 136 IMRT patients were propensity score matched with 136 PBT patients. In the matched groups, a greater proportion of the IMRT patients (55/136, 40.4%) developed grade 4 lymphopenia during nCRT compared with the PBT patients (24/136, 17.6%, P  < 0.0001). On multivariable analysis, PBT was significantly associated with a reduction in grade 4 lymphopenia risk (odds ratio, 0.29; 95% confidence interval, 0.16–0.52; P  < 0.0001). Conclusion: PBT is associated with significant risk reduction in grade 4 lymphopenia during nCRT in esophageal cancer.